2011
DOI: 10.1016/j.mambio.2010.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Forage use in domestic cattle (Bos indicus), capybara (Hydrochoerus hydrochaeris) and pampas deer (Ozotoceros bezoarticus) in a seasonal Neotropical wetland

Abstract: a b s t r a c tThe impact of livestock grazing on native wildlife remains a topic for considerable debate. In the Brazilian Pantanal extensive cattle ranching has been practised since the mid-18th century and cattle live alongside a diverse group of medium to large sized terrestrial mammalian herbivores. This study examined the use, similarity and selection of forage resources among cattle (Bos indicus), pampas deer (Ozotoceros bezoarticus) and capybara (Hydrochoerus hydrochaeris) in a paddock in the central r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 30 publications
2
22
0
1
Order By: Relevance
“…; Desbiez et al. ). Non‐linear relations between woody plant and species diversity reflect a transitional phase of the encroachment, as the shrub islands stage (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…; Desbiez et al. ). Non‐linear relations between woody plant and species diversity reflect a transitional phase of the encroachment, as the shrub islands stage (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In Brazil, a 2-year study comparing the diets of pampas deer, cattle, and capybaras (Desbiez et al 2011 ) found that all three species preferred L . hexandra and H .…”
Section: Potential Competition With Cattlementioning
confidence: 99%
“…However, the authors conclude that the presence of cattle is not signi fi cantly detrimental to capybaras or deer in terms of diet competition. In general, Desbiez et al ( 2011 ) Exclusion plot experiments have been used to evaluate the impact of predators on prey species (Macdonald et al 1999 ) as well as the effect of herbivores on their target vegetation. Barreto ( 1994 ) carried out exclusion experiments to assess the impact of capybaras on their main resource, including in the experimental design total exclusion (TE, i.e., neither cattle nor capybaras could have access to the grasses), and capybara-only exclusion (only capybaras have access to the grass, PE).…”
Section: Potential Competition With Cattlementioning
confidence: 99%
“…This mass extinction of large mammalian herbivores most probably resulted in changes in the structure and species composition of the vegetation of the New World (Janzen & Martin, ; Doughty et al ., ). Later, the introduction of domestic livestock has also led to biodiversity loss in plants and animals (Steinfeld et al ., ) and is considered a serious threat to ecosystems (Desbiez et al ., ). However, in most areas of South America, including the Brazilian Pantanal, livestock may be filling a nearly empty niche because of the current unusual scarcity of large native herbivores relative to the Pleistocene and Neogene, at least partially replacing the functions of the lost megafauna (Pott & Pott, ; Pires et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, studies in the Pantanal have shown that the introduction of cattle farming c . 200 years ago (Desbiez et al ., ) has had relatively little impact on vegetation structures (Pott & Pott, ), whereas others have shown impacts such as increasing deforestation and species loss (Alho, Lacher & Goncalves, ; Seidl, de Silva & Moraes, ).…”
Section: Introductionmentioning
confidence: 99%